PENGARUH INTENSITAS MODAL, INVENTORY INTENSITY DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE - Putri, Lutviana Cindy Eka; Pratiwi, Adhitya Putri (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
The purpose of this research is to determine the effect of capital intensity, inventory intensity and transfer pricing on tax avoidance in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 20162020. The methodology used in this study is quantitative. The sampling technique used is purposive sampling and the sample obtained in this study is 90 data. The analytical method used is descriptive statistical analysis, classical assumption test, multiple regression analysis, determinant coefficient test, F test, and T test with the help of Eviews 9 software. Based on the test results, it was found that capital intensity, inventory intensity and transfer pricing had a simultaneous effect on tax avoidance. Capital intensity did not have an effect on tax avoidance. Inventory intensity had an effect on tax avoidance. Transfer pricing had no effect on tax avoidance.